1997
DOI: 10.1093/jnci/89.17.1277
|View full text |Cite
|
Sign up to set email alerts
|

Tobacco, alcohol, and socioeconomic status and adenocarcinomas of the esophagus and gastric cardia

Abstract: Because of the long lag time before risk of these tumors is reduced among ex-smokers, smoking may affect early stage carcinogenesis. The increase in smoking prevalence during the first two thirds of this century may be reflected in the rising incidence of these tumors in the past few decades among older individuals. The recent decrease in smoking may not yet have had an impact.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

40
331
8
14

Year Published

1998
1998
2007
2007

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 536 publications
(396 citation statements)
references
References 22 publications
40
331
8
14
Order By: Relevance
“…In the last 5 years, seven case -control studies have also been reported: five of them (Gammon et al, 1997;Zaridze et al, 2002) observed a higher risk for cardia cancers, while two did not , mixed site (C16.8) and site not otherwise specified (C16.9) gastric cancer. b 95% confidence intervals from multivariate Cox proportional models after adjusting for age, body mass index, alcohol intake and preference for saltiness in food.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the last 5 years, seven case -control studies have also been reported: five of them (Gammon et al, 1997;Zaridze et al, 2002) observed a higher risk for cardia cancers, while two did not , mixed site (C16.8) and site not otherwise specified (C16.9) gastric cancer. b 95% confidence intervals from multivariate Cox proportional models after adjusting for age, body mass index, alcohol intake and preference for saltiness in food.…”
Section: Discussionmentioning
confidence: 99%
“…An extensive review indicates that smoking is a moderate risk factor for gastric cancer (International Agency for Research on Cancer, 2004), but little support exists for an association with alcohol (Gammon et al, 1997;Sjödahl et al, 2006). The possibility of a differential effect of smoking and alcohol consumption on different gastric subsites, however, remains to be clarified.…”
mentioning
confidence: 99%
“…In 1993-95, histologically confirmed cases ages 30-79 years were identified by rapid ascertainment in three U.S. locations following Institutional Review Board approvals at the collaborating institutions [2], and written informed consent from each subject. Controls were selected from the same catchment areas by random-digit dial if under age 65 years or from the Medicare sampling frame if 65 or older.…”
Section: Methodsmentioning
confidence: 99%
“…Adenocarcinomas of the esophagus and stomach have diverse incidence patterns and risk factors [1], but cigarette smoking has been associated with both in some studies [2][3][4]. Polymorphisms in the glutathione-S-transferase (GST) and N-acetyltransferase (NAT) 1 genes, which are involved in Phase II detoxification of certain tobacco carcinogens, have been suggested as susceptibility factors but have not been consistently linked to elevated risks [5].…”
Section: Introductionmentioning
confidence: 99%
“…The 3 : 1 male predominance in oesophageal squamous-cell carcinoma is explicable by sex differences in the prevalence of the main risk factors, that is, use of tobacco and alcohol (Muir and McKinney, 1992;Gammon et al, 1997;Lagergren et al, 2000). However, no corresponding sex difference in the established risk factors for oesophageal or gastric adenocarcinoma can explain their male predominance (EUROGAST, 1993;Moller et al, 1994;Lagergren et al, 1999a, b;Kelley and Duggan, 2003;Crew and Neugut, 2004).…”
mentioning
confidence: 99%